Influence of mineral powders on the properties of binding systems - M. Sh. Salamanova; M. R. Nakhaev (Vestnik MGSU)
Introduction. Development of formulations of multicomponent binder compositions with the use of mineral additives of different nature is an urgent task. Multicomponent binders, “Portland cement – mineral additive”, “Portland cement – mineral additive – plasticizer” allow to expand the range of binders, to find economical practical application of resource-intensive material, to reduce energy consumption for high-temperature processing, and all this not to the detriment of the operational indicators of concrete and reinforced concrete.Materials and methods. According to the regulatory and technical documents GOST 31108, GOST 20515, it is recommended to use finely dispersed additives of both natural and anthropogenic origin as a component of binding systems, which do not have a harmful effect on the properties of cement paste and stone.Results. Topological models of multicomponent binder system, which differ depending on the nature and granulometry of mineral powder. On the basis of the conducted researches, the models of the diffusion interphase zone of cement stone, consisting of reacted clinker and mineral components, are presented; the boundary layers of which are characterized by the presence of calcium hydrate silicates and micropores of different configuration in the composition of neoplasms. The qualitative composition of the boundary interphase zone is determined by the nature and reactivity of the filler.Conclusions. The analysis of the results showed that the appropriate chemical and mineralogical composition, the presence of ion-exchange centers and high activity coefficient contribute to an increase in the reactivity of mineral additives, which is important for the creation of strong binder, necessary for the organization of monolithic high-rise construction with structural elements of complex hermetic configuration.